The Militarization of Turkish Foreign Policy - MEHMETCİK, HAKAN (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
Turkish Foreign Policy (TFP) has undergone structural changes over the last few years due to the perception of immediate threats to Turkish national security which, according to Ankara, has brought a need for a more assertive foreign policy. Consequently, Turkey is expanding its military presence in the Balkans, the Caucasus, the Middle East and Africa, and utilizing frequently coercive diplomacy to resolve foreign policy issues. This article analyses both the drivers and the consequences of the militarization of TFP. The main argument is that there are at least three drivers in this militarization, namely, the pursuit of strategic autonomy, the closing tandem between the domestic and foreign policy, and the Turkish military-industrial complex. The broader security and diplomatic consequences of TFP militarization in regional and international politics are also investigated.
Keywords: DOMESTIC POLITICS; TURKEY; MILITARY